It was a Supraclinoid Stenosis Rather Than Extracranial Carotid Stenosis - Chowdhury, RN; Rahman, KM; Khan, SU; Sarker, RN; Nabi, S; Siddiqui, MR; Mohammad, QD (Journal of Dhaka Medical College, 2011)
Carotid stenosis, both intracranial and extracranial is a significant risk factor for transient ischaemic attack and ischaemic stroke. Significant carotid stenosis increases the risk of artery to artery embolization. Duplex Ultrasound (USD) is a screening test for identification and grading of carotid stenosis. USD is less sensitive and specific than cerebral Digital Subtraction Angiogram (DSA) for evaluation of carotid stenosis. USD might underestimate or overestimate degree of carotid stenosis. Here a case is presented where USD found bilateral significant extracranial carotid stenosis, whereas DSA reported no right common carotid artery and left common carotid artery bifurcation stenosis rather there was significant 70% supraclinoid right internal carotid artery stenosis. Key words: Carotid stenosis; Supraclinoid stenosis; Duplex ultrasound examination; Digital subtraction angiogram DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8586 J Dhaka Med Coll. 2011; 20(1) :75-77